2016
DOI: 10.1002/pros.23234
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Proliferative Inflammatory Atrophy in Negative Prostatic Biopsies

Abstract: PIA finding in negative biopsies correlates with a decreased frequency of detecting PCa in men with persistent suspicion of PCa. The aggressiveness of future detected tumors was not associated with previous PIA finding. Prostate 76:1501-1506, 2016. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Some authors believe that PIA can progress to PC or HGPIN, being a PC precursor lesion [32,33]. However, some researchers have not demonstrated this association [34,35]. In canine prostatic pathology, HGPIN was previously reported to be frequently associated with canine PC [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors believe that PIA can progress to PC or HGPIN, being a PC precursor lesion [32,33]. However, some researchers have not demonstrated this association [34,35]. In canine prostatic pathology, HGPIN was previously reported to be frequently associated with canine PC [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…It is commonly in proximity to cancer, and proliferative inflammatory atrophy is proposed as a precursor to HGPIN and cancer. Like inflammation, studies on the association of atrophy and cancer showed both positive 35,44 and negative 45‐48 associations. In a prior study, 12 we showed that whenever atrophy abutted cancer, it was disproportionately close to Gleason pattern 3 cancer foci even after adjusting for the lesser frequency of higher‐grade cancer foci in the study.…”
Section: Discussionmentioning
confidence: 99%
“…A series of conditions are involved in the development of Prostate Cancer. The Proliferative Inflammatory Atrophy (PIA) occurrs initially due to prostatitis as a result of certain environmental factors and diet [4]. This condition may lead to the loss of epithelial cells and cause inflammation [5,6].…”
Section: Introductionmentioning
confidence: 99%